NAT10: An RNA cytidine transferase regulates fatty acid metabolism in cancer cells. Issue 9 (23rd September 2022) - Dalhat, Mahmood Hassan; Mohammed, Mohammed Razeeth Shait; Alkhatabi, Hind Ali; Rehan, Mohd; Ahmad, Aamir; Choudhry, Hani; Khan, Mohammad Imran
Abstract: Background: N ‐4 cytidine acetylation (ac4C) is an epitranscriptomics modification catalyzed by N ‐acetyltransferase 10 (NAT10); important for cellular mRNA stability, rRNA biogenesis, cell proliferation and epithelial to mesenchymal transition (EMT). However, whether other crucial pathways are regulated by NAT10‐dependent ac4C modification in cancer cells remains unclear. Therefore, in this study, we explored the impact of NAT10 depletion in cancer cells using unbiased RNA‐seq. Methods: High‐throughput sequencing of knockdown NAT10 in cancer cells was conducted to identify enriched pathways. Acetylated RNA immunoprecipitation‐seq (acRIP‐seq) and RIP‐PCR were used to map and determine ac4C levels of RNA. Exogenous palmitate uptake assay was conducted to assess NAT10 knockdown cancer cells using Oil Red O staining and lipid content analysis. Gas‐chromatography–tandem mass spectroscopy (GC/MS) was used to perform untargeted lipidomics. Results: High‐throughput sequencing of NAT10 knockdown in cancer cells revealed fatty acid (FA) metabolism as the top enriched pathway through the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis in differentially downregulated genes. FA metabolic genes such as ELOLV6, ACSL1, ACSL3, ACSL4, ACADSB and ACAT1 were shown to be stabilised via NAT10‐dependent ac4C RNA acetylation. Additionally, NAT10 depletion was shown to significantly reduce the levels of overall lipid content, triglycerides and total cholesterol. Further, NAT10 depletion in palmitate‐loaded cancer cells showed decrease in ac4C levels across the RNA transcripts of FA metabolic genes. In untargeted lipidomics, 496 out of 2 279 lipids were statistically significant in NAT10 depleted cancer cells, of which pathways associated with FA metabolism are the most enriched. Conclusions: Conclusively, our results provide novel insights into the impact of NAT10‐mediated ac4C modification as a crucial regulatory factor during FA metabolism and showed the benefit of targeting NAT10 for cancer treatment. Abstract : NAT10 is highly expressed in approximately 92% of cancer and it is related to cancer cell survival. NAT10 regulates fatty acid metabolism through ac4C‐mediated mRNA stability of ELOVL6, ACSL1, ACSL3, ACSL4, ACADSB and ACAT1. Targeting NAT10 could be beneficial for treating severe cancer cases driven by fatty acid metabolism.